Load flow study using fast decoupled method / Hairul Bahri Zahari - Zahari, Hairul Bahri (2004)
This thesis presents a framework that allows systematic studies on the hypothesis and derivations concerning the standard version of the fast decoupled load flow method using C programing language. Testings include studies on very simple systems, e.g. a3-bus transmission system. The 3-buses transmission system test result will be presented in this thesis and is considered as a base case which enables further modification of the presented network. Other results of the standard IEEE system is also presented (6bus,9 bus, and 14 bus).